4x-3=3(-1+x)

Simple and best practice solution for 4x-3=3(-1+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-3=3(-1+x) equation:


Simplifying
4x + -3 = 3(-1 + x)

Reorder the terms:
-3 + 4x = 3(-1 + x)
-3 + 4x = (-1 * 3 + x * 3)
-3 + 4x = (-3 + 3x)

Add '3' to each side of the equation.
-3 + 3 + 4x = -3 + 3 + 3x

Combine like terms: -3 + 3 = 0
0 + 4x = -3 + 3 + 3x
4x = -3 + 3 + 3x

Combine like terms: -3 + 3 = 0
4x = 0 + 3x
4x = 3x

Solving
4x = 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
4x + -3x = 3x + -3x

Combine like terms: 4x + -3x = 1x
1x = 3x + -3x

Combine like terms: 3x + -3x = 0
1x = 0

Divide each side by '1'.
x = 0

Simplifying
x = 0

See similar equations:

| x+6forx=13 | | 120=p+7p | | 2x-3=-4+x | | 3x+(4x-1)=90 | | 0.1t=.4+.3t | | 8m+m=90 | | X+2x-1=2(-1+x) | | (4x^2-9x-9)= | | -x^2+515x-7500=0 | | 10x-45=3(b-15) | | h(t)=196-16t^2 | | x^2+515x-7500=0 | | -3n+3(5n-4)=8n-2(-8n+6) | | 6n+2n=96 | | 5x-(8x+4)=8x+-15 | | 2z+9z=4z+45+22 | | 5x(8x+4)=8x-15 | | -2(8r+2)-5(1-2r)=-r-3-4r | | 2n+2u=p | | 5(2+2x)=9(x-3) | | -2-5=7n | | 27-u=172 | | 6-2n=4n+4 | | (5x^2-11x+4)= | | x^2+545x-7500=0 | | -3(2-5m)=2(7m-5) | | 6-x=4x+21 | | -7=7.37802(x)+(-4.9)(x^2) | | 5t-2=34-t | | 125+10x=230+2x | | (2q-3)q=27 | | 12y+6=12y+7 |

Equations solver categories